Factors Predicting Childbirth Self-Efficacy Among High-risk Pregnant Women - Mangkornpradit, Kanokon; Wongwiggan, Sugritta (NU Journal of Nursing and Health Sciences, 2023)
The purpose of this predictive correlation research study was to study the relationship factors and factors predicting childbirth self-efficacy among high-risk pregnant women. There were 200 women during their high risk in pregnancy with a gestational age between 28 to 41 weeks who received antenatal care in the obstetrics and gynecology outpatient department, at the Buddhachinaraj Phitsanulok Hospital, Phitsanulok province between May to December 2021. The sample size determines by power analysis method. The research instruments used, showing the reliability of Cronbach’s alpha coefficient, included The Thai Childbirth Self-Efficacy Inventory (0.96), the Wijma Delivery Expectancy/Experience Questionnaire (0.81), The symptom of Stress (0.92), and Social Support Questionnaire (0.80). The data were analyzed by descriptive statistics, Pearson correlation coefficient with Spearman rank correlation coefficient and multiple regression analysis by stepwise method. The result revealed that gravidarum and fear of childbirth had significant negative correlation with childbirth self-efficacy (r= -.160, p<.05 และ r= -.353, p<.01 respectively). Social support significant positive correlation with childbirth self-efficacy (r= .165, p<.05). Fear of childbirth and social support were found as good combine predictions of childbirth self-efficacy among high-risk pregnant women, with 12.6 of variance (R2 =.126, F =14.169, df=2, p< .001) and social support had the highest predicting childbirth self-efficacy (b=30.84, t=2.978, β=.199, p<.01). These results suggest that nurse and midwifery should promote social support and decrease fear of childbirth to enhance childbirth self-efficacy among high-risk pregnant women.